STUDENTS' MATHEMATICAL COMMUNICATION INSTRUMENTS: A GENDER PERSPECTIVE IN MATHEMATICS LEARNING - Mardiana Mardiana; Fredi Ganda Putra; Cornelia Victoria Anghel (Hipotenusa Journal of Research Mathematics Education (HJRME), 2025)
Evaluating students' mathematical communication ability is crucial for understanding their ability to convey mathematical ideas logically, precisely, and in a structured manner. A good evaluation instrument is the primary tool for measuring this aspect objectively and purposefully. This research is motivated by the low mathematical literacy achievement of Indonesian students in the 2018 PISA survey, which indicates weak mathematical communication ability. This study aims to analyze students' mathematical communication ability from a gender perspective. This study used a quantitative method with a survey design. The survey type used was a cross-sectional survey design. The results showed that female students had higher average scores than male students, but the ANOVA test produced a significance value of 0.621 (> 0.05), indicating no significant difference. This finding shows that mathematical communication ability is more influenced by individual factors. The implication is that teachers need to use adaptive learning approaches and evaluation instruments that address individual student needs.